Magic Ritual in Seneca’s Medea - Dikmonienė, Jovita (Literatūra, 2014)
The present article deals with the magic ritual in Seneca’s Medea. Seneca, following Ovid’sMetamorphoses, created in the tragedy a witchcraft scene which describes magic numbers, herbs, and rituals dedicated to Hecate. Unlike Ovid, Seneca focuses on rituals involving snakes, conjuring up the dead, and supernatural performative utterances, and emphasises the feeling of anger, which inspired Medea to practise infernal magic.In magic, Romans gave particular importance to the number “three” and the numbers that can be divided by three. Seneca also mentions these numbers. During the performance of the ritual by Medea, Hecate barks three times, a dragon with a trident tongue appears, and tripods play during the ritual. Medea sends to Creusa not two, as in Euripides’ tragedy, but three poisoned gifts: a robe, a necklace, and a crown. Seneca’s Medea makes a wreath to Hecate from nine snakes.Magical, hallucinogenic herbs play an important role in magic. Seneca, like Ovid in his Metamorphoses, describes Medea’s ritual whereby she prepares a magical blend of herbs to poison Creusa. Prometheus’ grass used by Medea is probably mandrake. However, Seneca, like Ovid, does not provide the exact names of the herbs used in magic.Some researchers argue that Seneca described the magic ritual in order to highlight Medea’s desire to control the environment. According to the author of the present article, this claim is only partially true. Magic was necessary for Medea not only to control the environment, but also to control herself. The magic ritual helped her to prepare herself for revenge by transforming her consciousness. With the help of magic her sorrow and pity were transformed into aggression, she overcame her fear and prepared herself to kill her children. Medea’s ritual can be described as the magic of the fight, because it allowed her to transform her consciousness into the fight mode.The description of the magic ritual served Seneca as the rhetorical means to induce fear in the reader and produce an ominous atmosphere of tragedy.